[OP.5D.06] HYPERTENSION AS A PATERNAL FACTOR INFLUENCES MATERNAL ADAPTATION TO PREGNANCY AND IS ASSOCIATED WITH PLACENTAL INSUFFICIENCY AND FETAL GROWTH RESTRICTION. (September 2016) - Barrientos, G.; Uceda, A.; Sgariglia, A.; Giardina, G.; Blois, S.M.; Toblli, J.E.
Abstract : Objective: Severe forms of hypertensive disorders of pregnancy, like early-onset preeclampsia (PE), are often linked with abnormal placentation. Genetic factors contributed by the father may be important for placental development, and previous studies support the existence of a paternal component for PE and fetal growth restriction. Thus, the present study was conducted to evaluate the influence of arterial hypertension as a paternal factor on placental development and fetal growth in normal female rats. Design and method: Female Wistar Kyoto rats (10–12 weeks old, N = 5animals/day analysed) were mated to congenic (WKYxWKY, control pregnancy) or Stroke-Prone Spontaneously Hypertensive Rat males (WKYxSHRSP, paternal effect model) and checked daily for vaginal plugs, denoted as gestation day (GD) 1. Maternal blood pressure (BP) was determined by the tail-cuff method pre-mating and on the morning of GD1, 7, 9, 13, 17 and 19. On the selected dates, females were housed in metabolic cages for collection of 24 h urine samples. Following collection of blood, animals were euthanized and implantation sites isolated for morphological analyses. Fetal and placental weights were recorded on GD18 and GD20. Results: Reproductive performance (Fig 1A) and maternal adaptations to pregnancy were impaired in females mated to hypertensive males. While BP in control dams showed slight variations, SBP rose suddenly in females pregnant from SHRSP males, peaking on GD9 and returning to pre-pregnancy levels at term (GD19, Fig 1B). WKYxSHRSP dams displayed a significant up-regulation of basal albumin excretion on GD14 (Fig 1C) respect to controls, consistent with defective renal function. Females pregnant from hypertensive males showed signs of placental insufficiency and FGR on GD18 and 20 (Fig. 1C-D). At mid pregnancy (GD14), morphological alterations were evident in the placenta, including an expansion of the labyrinth layer and thickened walls of the uterine spiral arteries. Figure. No caption available. Conclusions: Hypertension as a paternal factor influenced the kinetics of maternal blood pressure during pregnancy and compromised fetal growth, as a result of placental dysfunction. Identification of placental factors contributed by the paternal genotype may improve the understanding of disease mechanisms in hypertensive disorders of pregnancy.